Proposed Business Strategy to Strengthening Business of PT Tri Arjuna Ganesha (Case Study : Netizen Consultant) - Saputra, Alvin Augusto; Nirwandi, Maryat (The Indonesian Journal of Business Administration, 2015)
Abstract— Digital marketing become very popular these days. Most of people in the world now life in digital era. That phenomena can be seen from enormous internet user, social media user, and also smartphone user. Nowadays a lot of company trying to market their product or services using digital way because they see how powerful digital media. Internet users in Indonesia will grow rapidly to 123 million users by 2018 and in parallel with this growth, everything from e-commerce to online media to B2B applications will grow rapidly. Based on the long term plan of Netizen Consultant, Netizen Consultant calculate and decide they need to achieve their revenue target to develop and market the SaaS so the Sass will be fully ready on 2020. There is a huge gap between target revenue and actual revenue from Netizen Consultant’s financial report on 2014. Netizen Consultant management has a challenge to increasing their revenue so they can reach their long term target. The analysis was performed to the internal and external aspects of the Netizen Consultant. Internal analysis was done by using Value Chain analysis, resource analysis, and VRIO analysis. While external analysis was done by using PEST analysis, Porter's 5 Forces analysis, and Market analysis. Results of internal and external analyzes will be used to propose Directional strategy, and TOWS matrix to produce Functional strategy.Having obtained the strategy Functional, those strategies must be implemented in order to show significant changes. The result of the implementation plan will be use as guidence for Netizen Consultant in the implementation of the Functional strategy. Making the plan implementation is done by using the Balance Scorecard, financial projections until 2020, and action plans.Keywords: business strategy, company strategy, digital industry